Caloric restriction stimulates autophagy in rat cortical neurons through neuropeptide Y and ghrelin receptors activation - Ferreira-Marques, Marisa (2016)
Caloric restriction is an anti-aging intervention known to extend lifespan in several experimental models, at least in part, by stimulating autophagy. Caloric restriction increases neuropeptide Y (NPY) in the hypothalamus and plasma ghrelin, a peripheral gut hormone that acts in hypothalamus to modulate energy homeostasis. NPY and ghrelin have been shown to be neuroprotective in different brain areas and to induce several physiological modifications similar to those induced by caloric restriction. However, the effect of NPY and ghrelin in autophagy in cortical neurons is currently not known. Using a cell culture of rat cortical neurons we investigate the involvement of NPY and ghrelin in caloric restriction-induced autophagy. We observed that a caloric restriction mimetic cell culture medium stimulates autophagy in rat cortical neurons and NPY or ghrelin receptor antagonists blocked this effect. On the other hand, exogenous NPY or ghrelin stimulate autophagy in rat cortical neurons. Moreover, NPY mediates the stimulatory effect of ghrelin on autophagy in rat cortical neurons. Since autophagy impairment occurs in aging and age-related neurodegenerative diseases, NPY and ghrelin synergistic effect on autophagy stimulation may suggest a new strategy to delay aging process.